Editorial: Case reports in heart failure and transplantation: 2022 - Cameli, Matteo; Landra, Federico (Frontiers in Cardiovascular Medicine, 2023)
In this editorial we summarize the most viewed and downloaded contributing articles to the Research Topic “Case Reports in Heart Failure and Transplantation: 2022” of the journal Frontiers in Cardiovascular Medicine.